Digital Ruble: Assessing the Criminological Risks of the Proposed Model - Khisamova, Zarina; Sidorenko, Elina; Inozemtsev , Maxim; von Arx, Pierre (Law, State and Telecommunications Review, 2022)
[Purpose] The article deals with the prospects of introducing the digital ruble within the territory of the Russian Federation. [Methodology/Approach/Design] The methodological basis of this study is a set of methods of scientific knowledge, among which the main place is taken by the methods of historicism, consistency, analysis and comparative law. Having conducted a detailed review of global trends in this area, authors identified the main reference points that are relevant for most countries where pilot CBDC projects are being implemented. [Findings] The analysis of the key report, issued by the Central Bank of Russia, on the prospects for introducing the digital ruble allowed us to assess the architecture of the models proposed by the Central Securities Market, their advantages, and their disadvantages. [Practical Implications] Taking into account the assessment of statistical indicators on the Russian crime rate, the state of Russian criminal legislation, the concerns of institutional market participants, and the positions of mega regulators around the world, a criminological analysis of the potential risks of introducing the digital ruble was made. [Originality] The results of the study will be useful to both legal scholars who deal with issues of comparative law, and for practical specialists. the article provides detailed explanations about the theoretical and applied aspects of the introduction of the digital ruble. For the first time, the authors gave a theoretical justification for the risks associated with the introduction of a digital currency.